2020
DOI: 10.1111/raq.12425
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing suspended solids in intensive salmonid aquaculture: a review

Abstract: The intensive aquaculture of salmonids is a relatively young discipline within the animal husbandry sector. It differs to terrestrial livestock farming in one obvious and fundamental aspect – the aquatic environment. Besides great advantages such as buoyancy, the fluid medium also poses specific challenges for fish and fish farmers. One issue identified as a central problem in aquaculture is the presence of undissolved particulate matter in the water column. The ideal of fish living in pure, transparent water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 208 publications
(267 reference statements)
0
37
0
Order By: Relevance
“…Under the current challenges of a high population, aquaculture presents a safe and healthy food source ( Dawood et al, 2021 ). However, sustainable production of aquatic organisms has to consider the intensive and super-intensive farming systems ( Schumann and Brinker, 2020 ). Indeed, intensive systems could afford high production yields from the lowest possible unit of water ( Van Doan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the current challenges of a high population, aquaculture presents a safe and healthy food source ( Dawood et al, 2021 ). However, sustainable production of aquatic organisms has to consider the intensive and super-intensive farming systems ( Schumann and Brinker, 2020 ). Indeed, intensive systems could afford high production yields from the lowest possible unit of water ( Van Doan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining blood pH homeostasis is crucial for protein stability and enzyme function (Aboagye & Allen, 2018). In our study, the blood alkalosis found in treatments T500, T750 and T1000 on day 1 and T250 and T500 on day 5 was possibly related to TSS presence, which may hinder oxygen uptake in the fish (Schumann & Brinker, 2020). As the dissolved oxygen levels in the water remained similar between treatments, its direct effects on blood alkalosis were ruled out, leaving the hypothesis of possible functional hypoxia caused by TSS presence in the water, which would have interfered with the O 2 uptake.…”
Section: Methodsmentioning
confidence: 62%
“…Thus, such concentrations must be known for different fish species in aquaculture systems. The main effects of high TSS concentrations are skin irritations, fin erosion, blockage of the opercular cavity, gas diffusion inhibition, nitrogen compound excretion and changes in ion exchange (Holanda et al, 2020; Schumann & Brinker, 2020). In our study, the TSS concentrations that caused mortality in pacu juveniles were extremely high (6000 and 7000 mg L −1 ), which is rarely maintained in a culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the 450 kg tons of fish in the system producing ca. Forty-five kilogram dry weight solids with a theoretical average P of 23.9 mg/g dry weight ( Schumann and Brinker, 2020 ), the solids treatment system encountered a theoretical P load of 1.08 kg. This resulted in ca.…”
Section: Discussionmentioning
confidence: 99%